Pengaruh Kepemimpinan dan Supervisi Kepala Sekolah Terhadap Kinerja Guru di SMK Negeri 8 Medan - Aman Simaremare; Ngatmini Ngatmini; Zuraida Lubis (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
This study aims to analyze the influence of principal leadership and academic supervision on teacher performance at SMK Negeri 8 Medan. The research method used a quantitative approach with an ex post facto correlational design. The study sample consisted of 80 teachers selected using proportional random sampling. The research instrument was a questionnaire with a Likert scale. The data analysis technique used multiple linear regression. The results showed that (1) principal leadership had a significant positive effect on teacher performance (p < 0.05), (2) principal supervision had a significant positive effect on teacher performance (p < 0.05), and (3) leadership and supervision simultaneously had a significant effect on teacher performance with a determinant contribution of 56%. Thus, improving teacher performance at SMK Negeri 8 Medan is strongly influenced by the quality of the principal's leadership and supervision.